P0309IMPACT OF ACUTE KIDNEY INJURY ON CLINICAL COURSE AND TREATMENT RESPONSE IN PATIENTS WITH MINIMAL CHANGE NEPHROTIC SYNDROME. (6th June 2020) - Okushima, Hiroki; Iwata, Yukimasa; Takatsuka, Taisuke; Yoshimura, Daisuke; Kawamura, Tomohiro; Ueda, Yoshiyasu; Shoji, Tatsuya; Hayashi, Terumasa
Abstract: Background and Aims: Minimal change nephrotic syndrome (MCNS) has acute onset and is occasionally complicated with acute kidney injury (AKI) in its clinical course. Few studies concerning factors associated with AKI and impact of AKI on clinical course and response to treatments are available to date. Thus, we assessed the prevalence of and factors associated with AKI and its effect on clinical course in MCNS patients. Method: Single center retrospective cohort study was conducted on 72 biopsy-proven MCNS patients presented to Osaka General Medical Center, between January 2006 and December 2016. Multivariate logistic regression analysis and Cox proportional hazards analysis were used to assess contributing factors to AKI and its effect on the duration until remission. Results: Median age was 58 years and 50% were male. At first presentation, the mean albumin and total cholesterol were 1.7±0.5g/dl and 402±118mg/dl, respectively. The mean urinary protein and eGFR were 12.8±8.2g/gCr and 60.1±29.4ml/min/1.73m 2, respectively. A total of 29 patients (40%) had AKI and 10 of them needed renal replacement therapy (RRT). Corticosteroid and cyclosporine A were used in 66 (91%) and 3 (4%) patients, respectively for initial treatment and 3 patients (4%) received neither. 67 patients (93%) achieved complete remission (CR) with a median duration of 18 days after treatment, while 20 of those relapsed during the median follow-up period of 38 months. Logistic regression analysis revealed that older age, lower albumin, and higher urinary protein were significantly associated with AKI. Furthermore, patients with AKI had longer duration to CR induction compared with those without AKI (Log-rank test: p=0.03). Cox proportional hazards analysis showed that older age and RRT induction were associated with the delay of CR. Conclusion: AKI occasionally occurs in patients with MCNS and need for RRT is associated with the delay of CR.